2014
DOI: 10.1007/s00221-014-3958-1
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol exposure inhibits adult neural stem cell proliferation

Abstract: Alcohol exposure can reduce adult proliferation and/or neurogenesis, but its impact on the ultimate neurogenic precursors, neural stem cells (NSCs), has been poorly addressed. Accordingly, the impact of voluntary consumption of alcohol on NSCs in the subventricular zone (SVZ) of the lateral ventricle was examined in this study. The NSC population in adult male C57BL/6J mice was measured after voluntary alcohol exposure in a two-bottle choice task using the neurosphere assay, while the number of NSCs that had p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 62 publications
0
16
1
Order By: Relevance
“…Hansson et al ( 2010 ) in an adult rat 7 weeks chronic relapsing alcoholic model found that DCX+IR and SOX2+IR in the SVZ was reduced just after treatment and the reduced SVZ neurogenesis persisted for 21 days of abstinence. Other studies in adult mice have reported weeks of ethanol self-administration reduce SVZ BrdU+ cells (Campbell et al, 2014 ). We previously found that acute ethanol dose-dependently decreased cell proliferation in the SVZ of adolescent rats (Crews et al, 2006 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hansson et al ( 2010 ) in an adult rat 7 weeks chronic relapsing alcoholic model found that DCX+IR and SOX2+IR in the SVZ was reduced just after treatment and the reduced SVZ neurogenesis persisted for 21 days of abstinence. Other studies in adult mice have reported weeks of ethanol self-administration reduce SVZ BrdU+ cells (Campbell et al, 2014 ). We previously found that acute ethanol dose-dependently decreased cell proliferation in the SVZ of adolescent rats (Crews et al, 2006 ).…”
Section: Discussionmentioning
confidence: 92%
“…Further, studies suggest that drug-induced loss of neurogenesis contributes to addiction and recovery from a variety of drugs, including alcohol (Mandyam and Koob, 2012 ; Staples and Mandyam, 2016 ). Previous studies have found that chronic ethanol treatment of adult rats reduces NPC proliferation in the DG (Nixon and Crews, 2002 ; Herrera et al, 2003 ; He et al, 2005 ) and SVZ (Crews et al, 2004 ; Hansson et al, 2010 ; Campbell et al, 2014 ). A binge model of alcohol dependence found reduced adult hippocampal DG neurogenesis following ethanol treatment (Nixon and Crews, 2004 ; Hansson et al, 2010 ).…”
Section: Introductionmentioning
confidence: 97%
“…A recent study demonstrated that voluntary chronic alcohol consumption reduces BrdU retention in the SVZ but had no effect on mitotic cell types, suggesting a role of alcohol in controlling the dynamics of NSPC proliferation. These in vivo findings were supported by in vitro experiments, which found that direct exposure to high doses of alcohol significantly reduced neurosphere culture proliferation [126]. As the binge drinking of alcohol is often combined with the abuse of other addictive drugs, the combinations of alcohol with cocaine and 3,4-methylenedioxy-methamphetamine (MDMA) were also studied for their combined effects on NSPC survival.…”
Section: Modulation Of Nspcs By Addictive Drugs and Underlying Mechanmentioning
confidence: 95%
“…Neural stem cells (NSCs) have received much attention in recent years as a therapeutic candidate for many neurodegenerative diseases such as Parkinson's disease (PD) and Alzheimer's disease (AD) (Soldner et al, 2009;Swistowski et al, 2010;Kang et al, 2016), and much research has focused on uncovering the detailed mechanisms behind NSCs fate determination. NSCs have two main properties, first, they have unlimited self-renewal capacity throughout the lifespan of the organism (Akesson et al, 2008;Campbell et al, 2014), and secondly they are multipotent and can differentiate into all types of cells within the neuro-ectodermal lineages of central nervous system, for example, glia cells and a variety of neurons (Chiasson et al, 1999). NSC fate is affected by extracellular and intracellular factors, especially the particular microenvironment in which the NSC is located as well as metabolic state of the cell (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%